COUNSELING ON QURBANI PROCEDURES - Taufikurrahman Yasin; Arief Hidayat Efendi; Nina Triana Murti; Retno Widyani; Baston; Fitri Dian Perwitasari; Mus Nilamcaya; Bayu Arisandi (Ann Publisher, 2024)
Socialization of the Slaughter of Sacrificial Animals following Islamic law and for the sake of public health is a form of community service. One of the purposes of this activity is to provide briefings on how to choose good sacrificial animals and how to slaughter and handle sacrificial meat following sharia. The target of this PPM activity is the mosque or musholla ta'mir in Cirebon, high school students in charge of spirituality, the organizing committee, and students. This community service activity took place on June 12, 2024, from 08.00 to 12.00 with counseling presented and assisted by audiovisuals. The socialization activity of slaughtering sacrificial animals received enthusiasm from the participants with a discussion session with three speakers. The message from the participants is that this activity can be carried out 30 days before the Eid al-Adha celebration so that they can choose sacrificial animals according to Islamic law.